1999
DOI: 10.1073/pnas.96.4.1480
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana proton transporters, AtNhx1 and Avp1, can function in cation detoxification in yeast

Abstract: Overexpression of the Arabidopsis thaliana vacuolar H ؉ -pyrophosphatase (AVP1) confers salt tolerance to the salt-sensitive ena1 mutant of Saccharomyces cerevisiae. Suppression of salt sensitivity requires two ion transporters, the Gef1 Cl ؊ channel and the Nhx1 Na ؉ ͞H ؉ exchanger. These two proteins colocalize to the prevacuolar compartment of yeast and are thought to be required for optimal acidification of this compartment. Overexpression of AtNHX1, the plant homologue of the yeast Na ؉ ͞H ؉ exchanger, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
375
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(390 citation statements)
references
References 34 publications
7
375
1
1
Order By: Relevance
“…In yeast, Nhx1 is found on a prevacuolar compartment (PVC) and is involved in salt tolerance by mediating Na ϩ sequestration in the PVC. The AtNHX1 cDNA is able to complement some of the phenotypes of the yeast nhx1 mutant (Gaxiola et al, 1999), and overexpression of AtNHX1 in Arabidopsis conferred salt tolerance on the transgenic plants (Apse et al, 1999). However, subcellular localization of the protein in plants indicated that it is in fact a tonoplast protein (Apse et al, 1999), and its ability to complement the yeast mutant may reflect its mislocalization to the PVC upon heterologous expression.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 94%
See 1 more Smart Citation
“…In yeast, Nhx1 is found on a prevacuolar compartment (PVC) and is involved in salt tolerance by mediating Na ϩ sequestration in the PVC. The AtNHX1 cDNA is able to complement some of the phenotypes of the yeast nhx1 mutant (Gaxiola et al, 1999), and overexpression of AtNHX1 in Arabidopsis conferred salt tolerance on the transgenic plants (Apse et al, 1999). However, subcellular localization of the protein in plants indicated that it is in fact a tonoplast protein (Apse et al, 1999), and its ability to complement the yeast mutant may reflect its mislocalization to the PVC upon heterologous expression.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 94%
“…One example of a transporter that appears to be localized differently in yeast and plants has been described recently (Apse et al, 1999;Gaxiola et al, 1999). AtNHX1 from Arabidopsis is a member of a family of intracellular Na ϩ /H ϩ exchangers and was identified based on sequence similarity to yeast Nhx1.…”
Section: Are Plant Cells Just Yeast Cells With Chloroplasts?mentioning
confidence: 99%
“…Although the detailed molecular mechanism remains obscure, with regard to the known functions of Sec22p and its potential additional link to the vacuole, it may be involved in targeting transporters or transport specificity-modulating proteins to alter the efficacy of cation sequestration to the vacuole. Potential targets to be altered at the tonoplast are the H þ /cation exchange proteins Vnx1p and Nhx1p [35][36][37] . In addition, the loss of sec22D could lead to mistargeting of such proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of NHX1 is induced by salinity and ABA in Arabidopsis (72,73), rice (74) and cotton (75). The expression level of NHX1 is correlated with genotypic differences in salt tolerance in cotton (75).…”
Section: Sodium Compartmentationmentioning
confidence: 99%
“…Complementation studies showed that AtNHX1 (72) and OsNHX1 (69) The SOS pathway and ABA regulate AtNHX1 gene expression and its antiporter activity under salt stress. The promoter of AtNHX1 contains putative ABA responsive elements (ABRE) between -736 to -728 from the initiation codon.…”
Section: Sodium Compartmentationmentioning
confidence: 99%